THE IMPLEMENTATION OF ISLAMIC PARENTING TO ENHANCE RESILIENCE IN ORPHANS AT AL-JAM’IYATUL WASHLIYAH ORPHANAGE IN MEDAN - Harahap, Zul Ilfah; Sahrul (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2025)
This study explores the implementation of Islamic parenting in fostering resilience among orphans at Al-Jam'iyatul Washliyah Orphanage in Medan. A descriptive qualitative method with a case study approach was utilized to obtain an in-depth understanding of the phenomenon. Participants consisted of caregivers, foster children, and orphanage staff members who were directly involved in caregiving activities. Data were gathered through semi-structured interviews, direct observation, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that Islamic parenting characterized by role modeling (al-uswah), habituation of worship (al-‘adah), provision of advice (al-mau’izhah), attentiveness (al-mulahazhoh), and non-violent discipline (al-‘uqbah), contributed significantly to enhancing the orphans’ resilience across psychological, social, and academic domains. These methods supported the development of emotional regulation, self-discipline, empathy, social connectedness, and spiritual awareness. Caregivers functioned not only as educators but also as surrogate parents who provided moral direction, emotional security, and consistent routines. The study concludes that Islamic parenting practices hold potential as a strategic framework for strengthening resilience in institutional care settings. Their adoption in other orphanages or childcare institutions may offer valuable benefits in promoting the psychological well-being and holistic development of children affected by loss, abandonment, or economic hardship.